SISTEM INFORMASI SARANA DAN PRASARANA UNIVERSITAS TEKNOLOGI SUMBAWA BERBASIS WEB MENGGUNAKAN METODE SPIRAL - W, Yunanri; Sasmita Susanto, Eri (Teknik Informatika, Institut Teknologi Nasional malang, 2022)
The development of information technology is rapidly expanding to all lines in 2021, showing that there are 202.6 million users of information technology in Indonesia, out of 73.7% of the total population of Indonesians who use the internet to search for information. Indonesia's population is 274.9 million, and those who use the internet are 202.6 million. This is a good opportunity to develop an information system, one of which is in the realm of education. Education is one of the main actors in the development of human resources to make individuals who have qualities and abilities. The spiral model used in software development methods: communication, planning, risk analysis, engineering, construction and launch, customer evaluation. The results of this study The testing was carried out using the black box method. includes using the spiral method, including registration features, logins, user transactions, loan management can be done by showing an average 100% trial success that goes well.